FACTORS AFFECTING SUCCESSFUL FROZEN EMBRYO TRANSFER IN CATTLE UNDER FARM CONDITION - MISHRA, G K; SINGH, NARINDER; SIDDIQUl, M U; SHUKLA, M K; SAXENA, S K (The Indian Journal of Animal Reproduction, 2023)
Embryo transfer technology (ETT) helps in tho dissemination of best germ plasm of both male and female whereas artificial insemination Al) disseminates only male genotype. The aim of present study is to evaluate the variables affecting pregnancy rate following non-surgical embryo transfer in crossbred and indigenous cattle under farm condition. A total of 48 frozen embryos were transferred into as many reciplents which resulted in overall 20.83 per cent pregnancy rate. The study revealed that transfer of embryos into anterior one third of uterine horn resulted in significantly (P < 0.05) higher pregnancy rate (34.62%) compared to the posterior two third of uterine horn (4.55%). The results indicated that the site of embryo deposition in uterine horn has significant influence on the pregnancy rate in cattle.